Scaling Early Childhood Digital Practices Through a Design-Based Implementation Research Model in Rural Ecosystems - Erie Siti Syarah; Kristanti Ambar Puspitasari; Siti Aisyah; Noviana Mustapa; Sudirman Sudirman; Linawati Linawati; Nursyahidah binti Khalid; Musakkid Himphinit (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study examines how a design-based implementation research (DBIR) approach can accelerate developmentally appropriate digitalization in early childhood education within a rural village ecosystem. We co-designed, piloted, and iteratively refined a practice-proximal package, professional learning and coaching, a contextualized digital lesson bank, implementation tools (rubrics/SOPs), and organizational supports, delivered through a stepped-wedge rollout across six ECE centers (310 children; 34 staff). Mixed methods integrated repeated surveys/logs, structured classroom observations and artefact audits, and interviews/FGDs; instruments covered teacher outcomes, classroom processes, center-level implementation outcomes, and system supports. Quantitatively (n=18 teachers), teachers strongly endorsed play-based pedagogy and age-appropriate management and reported high confidence to blend traditional–digital approaches, while routine device/app use and simple media creation were lower, indicating an enactment fluency gap. Qualitatively, key barriers were limited devices/media, uneven digital skills, and device-related classroom management; children’s engagement was predominantly positive. Triangulation suggests two proximal mechanisms, motivation and procedural clarity, by which coaching and SOPs (rotation/transition) convert enthusiasm into on-task behavior. Findings yield a feasible pathway for scale: prioritize shared-device solutions and offlineable media, intensify practice-based coaching on two workflow “kernels,” and institutionalize leadership-backed routines. Future work will test dose–response and moderation using longitudinal mixed-effects models and center-level interrupted time series to assess sustainment and generalizability.